Hawking Temperature of the Reissner-Nordstrom-Vaidya Black Hole - T. Triyanta; Anike N. Bowaire (Institute for Research and Community Services (LPPM) ITB, 2013)
We have derived the Hawking temperature of the Reissner-Nordstrom-Vaidya black hole by the use of both the radial null geodesic and the complex path methods. We have obtained that the mass dependence of the temperature in the Reissner-Nordstrom-Vaidya black hole is not as simple as that in the Schwarzschild black hole, but still we regain the conclusion, as in the case of the Schwarzschild black hole, that a higher Hawking temperature corresponds to a lower mass of a black hole.